(untitled) (Jurnal Penelitian, 2012)
Soren Kierkegaard and Muhammad Iqbal were philosophers who place human being as a starting point to seek the truth. This study was aimed to explore the meeting and parting point between the two. This study revealed that the existence of human being explained by them had a meeting point: it is that the two are theological-philosophy views. The unique of Kierkegaardís view concentrate on the analysis of existence, esthetic, ethics and religious step. Only those who dare to make a decision can exist because his own decision will drive him to his life goal. This view is the same as Muhammad Iqbalís view that Muslim has a responsibility for his own suffer. They are the only one who can change history into what they want. Iqbal saw the world as the product of human beingís effort. The existence order them to survive as a subject, person ñ as the representative of God (insan kamil).